Penggunaan Metode Card Sort dalam Meningkatkan Kemampuan Membaca pada Mata Pelajaran Bahasa Indonesia Di SD Negeri 1 Landbaw - Yulita Dwi Lestari; Ridho Agung Juwantara; Riska Alfiawati; Deviyanti Pangestu (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2024)
This research aims to determine the use of the Card Sort method in improving reading ability. Reading is a means for students to learn things that are not yet known and can expand knowledge, students can recognize themselves, their culture and even help recognize the culture of other people, and students can recognize written messages contained in reading. To achieve the above goals, students' ability to read is needed. The Card Sort method is a learning method used to help remember what they have read in reading books, not only from short-term memory to long-term memory. The problems in learning to read that occur in class IV SDN 1 Landbaw are that students cannot read well and correctly, students cannot answer questions related to information and reading material, and draw conclusions from the reading. As a result, most students are less active in concluding reading content, students also feel bored with learning to read so they are less enthusiastic about following it. The use of the Card Sort learning method is expected to be able to improve students' reading skills in accordance with the Class IV Minimum Completion Criteria (KKM) in Indonesian language subjects at SDN 1 Landbaw because in using the Card Sort method students are required to actively carry out responsibilities for the assigned tasks. given by the teacher. The results of research using the Card Sort method can improve students' reading skills. Learning with this method can improve the reading of class IV students at SDN 1 Landbaw. The average Card Sort method in student learning in Indonesian language subjects from the status cycle reached 60.50%, then in the second cycle it reached 80.50%, so there was an increase of 20%. In this case, students' reading increased by 45%. So with an increase in reading, 80% of students completed their studies and 20% of students who did not complete their studies.